Magic and the mind mechanisms, functions, and development of magical thinking and behavior - q (New York ; Oxford : Oxford University Press, 2010)
Subbotsky argues that the role of magical thinking in child development and in adult life should be reconsidered. In children, magical thinking is an important part of cognitive development. In adults, magical thinking assists individuals as they struggle with situations that are beyond rational control.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Magical thinking